Challenges in Community-Research Relationships: Learning from Natural Science in Nunavut - Gearheard, Shari; Shirley, Jamal (ARCTIC, 2009)
The context and conduct of Arctic research are changing. In Nunavut, funding agencies, licensing bodies, and new regulatory agencies established under the Nunavut Land Claims Agreement require researchers to engage and consult with Inuit communities during all phases of research, to provide local training and other benefits, and to communicate project results effectively. Researchers are also increasingly expected to incorporate traditional knowledge into their work and to design studies that are relevant to local interests and needs. In this paper, we explore the challenges that researchers and communities experience in meeting these requirements by reviewing case studies of three natural science projects in Nunavut. Together, these projects exemplify both success and failure in negotiating research relationships. The case studies highlight three principal sources of researcher-community conflict: 1) debate surrounding acceptable impacts of research and the nature and extent of local benefits that research projects can and should provide; 2) uncertainty over who has the power and authority to dictate terms and conditions under which projects should be licensed; and 3) the appropriate research methodology and design to balance local expectations and research needs. The Nunavut research licensing process under the Scientists Act is an important opportunity for communities, scientists, and regulatory agencies to negotiate power relationships. However, the standards and procedures used to evaluate research impact remain unclear, as does the role of communities in the decision-making process for research licensing. The case studies also demonstrate the critical role of trust and rapport, forged through early and frequent communication, efforts to provide local training, and opportunities for community members to observe, participate in, and derive employment from project activities. Clarifying research policies in Nunavut is one step to improving relations between scientists and communities. In addition, steps need ...